The influence of stress on fear memory processes - Martijena, Irene Delia (2012)
It is well recognized that stressful experiences promote robust emotional memories, which are well remembered. The amygdaloid complex, principally the basolateral complex (BLA), plays a pivotal role in fear memory and in the modulation of stress-induced emotional responses. A large number of reports have revealed that GABAergic interneurons provide a powerful inhibitory control of the activity of projecting glutamatergic neurons in the BLA. Indeed, a reduced GABAergic control in the BLA is essential for the stress-induced influence on the emergence of associative fear memory and on the generation of long-term potentiation (LTP) in BLA neurons. The extracellular signal-regulated kinase (ERK) subfamily of the mitogen-activated protein kinase (MAPK) signaling pathway in the BLA plays a central role in the consolidation process and synaptic plasticity. In support of the view that stress facilitates long-term fear memory, stressed animals exhibited a phospho-ERK2 (pERK2) increase in the BLA, suggesting the involvement of this mechanism in the promoting influence of threatening stimuli on the consolidation fear memory. Moreover, the occurrence of reactivation-induced lability is prevented when fear memory is encoded under intense stressful conditions since the memory trace remains immune to disruption after recall in previously stressed animals. Thus, the underlying mechanism in retrieval-induced instability seems not to be functional in memories formed under stress. All these findings are indicative that stress influences both the consolidation and reconsolidation fear memory processes. Thus, it seems reasonable to propose that the emotional state generated by an environmental challenge critically modulates the formation and maintenance of long-term fear memory.